Impact of Salinity on the Growth of Potato Solanum tuberosum L. Cultivated in Vitro Conditions - Faraj Atiyah; Rabihah Hamad; Munyah Hammad (AlQalam Journal of Medical and Applied Sciences, 2025)
Soil salinity is a growing problem worldwide, threatening agricultural productivity. This research has been done to try to solve it by studying the "Impact of salinity on the growth of potato Solanum tuberosum L." cultivated in vitro conditions. In August and September of 2022, this study was conducted in the Faculty of Science laboratory at Omar Al-Mukhtar University in Libya. Seven different concentrations of sodium chloride were used as treatments. The study used a completely unexpected design: NaCl concentrations were as follows: 10 mM, 30 mM, 50 mM, 70 mM, 100 mM, and 120 mM (Control). To cultivate a single-node stem cutting of a single potato cultivar (Spunta), they made use of MS medium treated with these amounts of NaCl. Investigating various growth characteristics, such as plantlet height, number of leaves/plantlets, number of roots/plantlets, and shoot weight, was the goal. There were notable variations across the treatments; as salinity rises, the majority of the studied parameters fall to their lowest values.